A Medico Legal Study of Fetal Deaths in and Around Guntur - A.Krishnajaneyulu; N. Devchand; Raja Sekhar Uppu; T.T.K.Reddy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: There are quite a number of foetal deaths occurring in the developing country like India due to low socio economic status, illiteracy, ignorance, lack of interest, concealment of the birth, having female child etc. This is despite the fact that these occurrences are a world- wide phenomenon and by definition involve criminal law concerns such as illegal abortion, concealment of birth, murder, or neonaticide and abandonment of babies. This study is to make comprehensive and analytical study of various medico legal aspects of foetal and infant deaths in and around Guntur district during the period of 2013-2015.Materials and methods: This is a three year retrospective study of autopsies done on the foetus and infants at the Department of Forensic Medicine, GMC/GGH Mortuary, Guntur from 2013 to 2015. Inquest and autopsy findings are analyzed to evaluate demographic profile and various socio-economic factors contributing to the foetal deaths, the pattern of injuries, manner & cause of death of the foetuses, neonates and infants. Observations and conclusion: Total number of cases of foetal autopsy amounts to around 1.2 % of total autopsy during the study period but in the study, relatively large number i.e., 50% of cases of abortuses, foetuses and newborns indicated that the manner had been homicidal or death by abandonment. Female foetal autopsies amounted to about 52% of total foetal autopsies and homicidal male foetal deaths are 56% of total homicidal foetal deaths. This study is helpful to the investigating authorities to identify such cases for further investigation of the cases.